Anesthesiological risks in mucopolysaccharidoses - Alessandra Moretto; Maria Grazia Bosatra; Laura Marchesini; Simonetta Tesoro (BMC, 2018)
Abstract Background Patients suffering from mucopolysaccharidosis are among the most complex from the anesthesiological point of view, especially regarding the management of the airway. The evidence base for anesthesia management is often limited to case reports and small case series. Aims To identify useful information about experience with each subtype of mucopolysaccharidosis reported in the literature and propose a guide on the best options for airway management to the anesthesiologists who take care of these patients. Methods A query of the PubMed database specific for "anesthesia" and "mucopolysaccharidosis" and a further query specific for "mucopolysaccharidosis and difficult airway management" was conducted. We looked for those items that offered practical guidance to anesthesiological management. We did not exclude case reports, especially those that reported a specific technique, because of their practical suggestions. Results We identified 15 reviews, 17 retrospective case series, 5 prospective studies, and 28 case reports that focused on airway managements in anesthesia or had practical suggestions for preoperative evaluation and risk assessment. An accurate preoperative evaluation and the need for an experienced team are emphasized in all the reviewed articles and for each type of mucopolysaccharidosis. Many suggestions on how to plan the perioperative period have been highlighted. Insertion of a laryngeal mask airway generally improves ventilation and facilitates intubation with a fiberoptic bronchoscope. Furthermore, the videolaryngoscope is very useful in making intubation easier and facilitating bronchoscope passage. Conclusions Patients with mucopolysaccharidosis are at high risk for anesthesia-related complications and require a high level of attention. However, a multidisciplinary approach, combined with expertise in the use of new techniques and new devices for airway management, makes anesthesiological management safer. Further research with prospective studies would be useful.